Answer : The equilibrium constant for this reaction is, [tex]K=\frac{(K_b)^2}{K_a}[/tex]
Explanation :
The given main chemical reaction is:
[tex]N_2(g)+2O_2(g)\rightarrow N_2O_4(g)[/tex]; [tex]K[/tex]
The intermediate reactions are:
(1) [tex]N_2O_4(g)\rightarrow 2NO_2(g)[/tex]; [tex]K_a[/tex]
(2) [tex]\frac{1}{2}N_2(g)+O_2(g)\rightarrow NO_2(g)[/tex]; [tex]K_b[/tex]
We are reversing reaction 1 and multiplying reaction 2 by 2 and then adding both reaction, we get:
(1) [tex]2NO_2(g)\rightarrow N_2O_4(g)[/tex]; [tex]\frac{1}{K_a}[/tex]
(2) [tex]N_2(g)+2O_2(g)\rightarrow 2NO_2(g)[/tex]; [tex](K_b)^2[/tex]
Thus, the equilibrium constant for this reaction will be:
[tex]K=\frac{1}{K_a}\times (K_b)^2[/tex]
[tex]K=\frac{(K_b)^2}{K_a}[/tex]
Thus, the equilibrium constant for this reaction is, [tex]K=\frac{(K_b)^2}{K_a}[/tex]